Factors influencing coronary artery target lesion revascularization after drug-coated balloon angioplasty - Undarsa, Alberta Claudia; Saboe, Aninka; Tiksnadi, Badai Bhatara; Akbar, Mohammad Rizki; Yahya, Achmad Fauzi (Frontiers in Cardiovascular Medicine, 2024)
Background Concerns regarding restenosis after treatment with drug-coated balloons (DCB) remain. We aimed to identify the incidence of target lesion revascularization (TLR) and explore clinical, procedural, and other factors influencing it. Methods Single-center retrospective analysis of a prospective cohort PCI registry study included 80 patients (100 lesions) who underwent successful DCB angioplasty between January 2020 and October 2023 and follow-up angiography within 2 years of either planned or unplanned reason. Incidence and factors associated with TLR were analyzed. Results Angiographic evaluation was conducted within a median of 151 days (interquartile range: 109 days). During index procedure, 54% were complex lesions. Intravascular imaging (IVI) was performed in 80% of lesions. TLR occurred in 11% of the lesions and was less frequent in the IVI group compared to the angiography-alone group [6.3 vs. 54.5%; odds ratio: 0.156, 95% confidence interval (CI): 0.042–0.580; p = 0.002]. No association was found between baseline and lesion characteristics, lesion complexity, plaque morphology, pre-dilatation procedure balloon type, maximal inflation pressure, or length of DCB between the groups (p > 0.05). Multivariate analysis revealed that IVI utilization was independently associated with a lower TLR rate (adjusted odds ratio: 0.116, 95% CI: 0.020–0.669; p = 0.016). Conclusion In DCB angioplasty, only IVI use exhibited a significant difference in the TLR rate among baseline lesion characteristics and lesion preparation and was independently associated with a lower TLR rate.